Biological activities and chemical profiles of selected soil fungi isolated from Sirindhorn Peat Swamp Forest of Narathiwat, Thailand - Sukanya Dej-adisai; Narisorn Kaewchutima; Chatchai Wattanapiromsakul; Sathianpong Phoopha (Penerbit Universiti Kebangsaan Malaysia, 2021)
A total of 54 soil fungi were collected from Sirindhorn peat swamp forest in Narathiwat Province which is the last peat swamp forests in Thailand. They were extracted using four different solvents and 104 crude extracts were obtained. The bioactivity screening of these samples was done employing alpha-glucosidase inhibition, anti-inflammation using nitric oxide inhibition and cytotoxicity using cancer cell line (MCF-7). The results showed that SPSF224 crude extract had the best biological activities in the screening tests and was then selected for further study. The SPSF224 was identified as Penicillium maximae. The crude extracts of P. maximae were determined for chemical profile, IC50 value of alpha-glucosidase inhibition, antioxidant and antimicrobial activities against Staphylococcus aureus, Trichophyton mentagrophytes, and T. rubrum. This was the first report of chemical investigation and biological activity evaluation of P. maximae.